(untitled) (Journal of Medical & Health Sciences Review, 2025)
Salt stress limits crop productivity by negatively impacting plant growth. Avena sativa (oat) is particularly vulnerable to salinity, but phytohormones like Indole Acetic Acid (IAA) may help mitigate these effects. This study examined the impact of NaCl-induced salt stress on Avena sativa and evaluated the role of exogenously applied IAA in alleviating stress-related damage. Plants were subjected to varying NaCl concentrations, with and without IAA treatment. Morphological and anatomical traits, including plant height, biomass, stomatal density, and vascular structure, were analyzed. Salt stress significantly reduced growth parameters, but IAA application improved root development, stomatal density, and vascular robustness. The response to IAA was dose-dependent, with optimal benefits at specific concentrations. IAA mitigates the adverse effects of salt stress on Avena sativa, enhancing growth and anatomical structure. These findings highlight its potential as a stress regulator, warranting further molecular studies for crop improvement.